What are we measuring? Comparison of household food security indicators in the Eastern Cape Province, South Africa. Issue 2 (3rd March 2016) - Hendriks, Sheryl L.; van der Merwe, Corné; Ngidi, Mjabuliseni S.; Manyamba, Christopher; Mbele, Mondli; McIntyre, Angela M.; Mkandawire, Elizabeth; Molefe, Queeneth N.; Mphephu, Mulalo Q.; Ngwane, Lithle
ASTRACT: The development of national food security information systems is constrained by a lack of guidance on which indicators to use. This paper compares food security indicators across two seasons (summer and winter) in one of the most deprived areas of the Eastern Cape province of South Africa. The results show that only anthropometric indicators are sensitive enough to differentiate levels of food insecurity. The lack of consistent classification across indicators means that surveys must use a combination of food consumption and experience of hunger measures backed up by anthropometric measures. Targeting interventions is difficult if the measures cannot be relied on. Further investigation is needed to identify a suite of appropriate indicators for a national information and surveillance system.